Hubungan Tingkat Pengetahuan Remaja Tentang Kesehatan Reproduksi Dengan Fenomena Kekerasan Dalam Pacaran Di STIKes Telogorejo Semarang - Ahdiyatul Umroh; Desi Soraya; Qomariyah Qomariyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Introduction: DP3A Semarang City in 2023 there were 67 cases with 5 male victims and 62 female victims. Adolescents are vulnerable to experiencing dating violence, with a high level of curiosity adolescents seek information related to reproductive health, but have not received the correct information. So that a lack of understanding will result in behavior that can harm yourself, your partner and the environment. Objektive: The purpose of this study was to determine the relationship between adolescent knowledge about reproductive health and the phenomenon of dating violence at STIKES Telogorejo Semarang. Metode: This study used a quantitative method with a cross sectional approach. The instruments used were reproductive health and dating violence questionnaires. The population in this study amounted to 597 respondents. The sample in this study were 96 respondents using the snowball sampling technique. This study used bivariate and univariate analysis with the statistical test used, namely chi-square. Results: The results showed a p-value of 0.031 <a (0.05) so that Ha was accepted and H0 was rejected. This means that there is a relationship between the level of knowledge of adolescents about reproductive health and the phenomenon of dating violence. The results showed that a good level of adolescent health knowledge indicated good courtship behavior to be a positive value for adolescents. acts of violence that occur, namely, physical violence, psychological violence, and verbal violence. Women are more dominant as victims of violence because they feel too intimate and fall in love with their partners so they tend to use feelings rather than logic. This causes women to suffer more from violence that occurs in dating relationships. Suggestions for objects to be open-minded about information about reproductive health and cases of dating violence in their environment, especially parents, so that they understand more about the development of their children, especially those who have entered their teens.